From implicit to explicit: overcoming common barriers to teaching critical thinking through an innovative online module - Schmidt, Christina M.; Sarvary, Mark A.; St. Juliana, Justin R.; Specht, Chelsea D. (Frontiers in Education, 2026)
In higher education, critical thinking is a fundamental skill vital for academic success and future career readiness. Despite its recognized importance and expectations for proficiency, many college graduates are perceived as inadequately prepared, largely due to the implicit nature of its instruction and common barriers instructors face, such as time constraints and lack of training and resources. This study addresses both the need for explicit critical thinking instruction and instructors’ challenges by developing a discipline-independent online module for undergraduate students that can be readily integrated into existing courses. The module, piloted at Cornell University, helps students to both define critical thinking and recognize its importance, providing a foundational understanding that is applicable across disciplines. It includes reflective tasks, interactive scenarios, and videos to enhance students’ understanding and identification of how, when, and why the process of thinking critically is used during academic and non-academic situations. Assessment through pre- and post-module surveys revealed significant improvements in students’ confidence in identifying, recognizing, and utilizing critical thinking, especially among those with limited prior experience. These results demonstrate that an accessible, explicit approach to critical thinking instruction can effectively build students’ foundational understanding and confidence, offering a scalable solution to address the persistent gaps in critical thinking development across higher education.